2015
DOI: 10.2217/pgs.15.29
|View full text |Cite
|
Sign up to set email alerts
|

Update on Thiopurine Pharmacogenetics in Inflammatory Bowel Disease

Abstract: Azathioprine and 6-mercaptopurine remain pivotal therapies for the maintenance of disease remission in patients with Crohn's disease and ulcerative colitis. While thiopurine S-methyltransferase deficiency was the first pharmacogenetic phenomenon to be recognized to influence thiopurine toxicity and reliably predict leukopenia, it does not predict other adverse effects, nor does it explain most cases of thiopurine resistance. In recent years, a number of other genetic polymorphisms have received increasing atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 82 publications
(125 reference statements)
1
26
0
1
Order By: Relevance
“…Azathioprine is known for potential myelotoxicity, and variabilities in inter-individual or inter-diseases thiopurine metabolism may influence myelotoxicity. Thiopurine methyltransferase (TPMT), inosine triphosphate pyrophosphatase (ITPA), or NUDT15 gene variants may influence the effect of AZA on B cell precursor cells in the bone marrow of AAV patients [21]. As AZA prolonged B cell depletion time only in AAV patients but not in patients with CTD, it is unlikely that AZA-related myelotoxicity is a general mechanism leading to prolonged B cell depletion time.…”
Section: Discussionmentioning
confidence: 99%
“…Azathioprine is known for potential myelotoxicity, and variabilities in inter-individual or inter-diseases thiopurine metabolism may influence myelotoxicity. Thiopurine methyltransferase (TPMT), inosine triphosphate pyrophosphatase (ITPA), or NUDT15 gene variants may influence the effect of AZA on B cell precursor cells in the bone marrow of AAV patients [21]. As AZA prolonged B cell depletion time only in AAV patients but not in patients with CTD, it is unlikely that AZA-related myelotoxicity is a general mechanism leading to prolonged B cell depletion time.…”
Section: Discussionmentioning
confidence: 99%
“…AZA and 6-MP can convert to active metabolites 6-thioguanine nucleotides (6-TGNs) via multiple sequential anabolic reactions [3, 4], which (e.g., deoxythioguanosine triphosphate) can incorporate into double-stranded DNA to trigger futile mismatch repair and lead multiple types of cells (e.g., T lymphocytes) to apoptosis and subsequent resolution of inflammation [58]. Meanwhile, 6-MP and its metabolites can be methylated by thiopurine methyltransferase (TPMT) and interrupt intervening DNA synthesis [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…NUDT15 is deemed to dephosphorylate the thiopurine active metabolites TGTP and TdGTP, preventing their incorporation into DNA and negatively affecting the cytotoxic effects of thiopurines [2, 3, 14, 2124, 28, 3133]. Crystal structure of NUDT15 has been characterized, making it possible to estimate the impact of Arg139Cys and Arg139His on NUDT15 activity, and subsequent cell sensitivity to thiopurine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…TPMT*1 represents the wild-type allele with normal TPMT activity while *2, *3A, *3B, *3C, and *8 account for approximately 95% of all TPMT variants known to result in TPMT deficiency. 3 With the conventional dose of thiopurines, individuals who have inherited two copies of the inactive TPMT allele (homozygous deficient) experience severe myelosuppression. A significant proportion (30%-60%) of individuals who have inherited one copy of the inactive TPMT allele (heterozygous deficient) develop moderate-to-severe myelosuppression.…”
mentioning
confidence: 99%
“…NUDT15 is a nudix hydrolase that degrades 8-oxo-dGTP and 8-oxo-dGDP in vitro, suggesting that it prevents misincorporation of 8-oxo-2'-deoxyguanosine 5'-triphosphate (8-oxo-dGDP) into DNA in vivo. 3,18 In-vitro studies showed that treatment with 6-MP resulted in a higher percentage of apoptosis and necrosis in cells transfected with the NUDT15 R139C construct compared with cells with the wildtype construct. 14 We performed NUDT15 R139C testing by polymerase chain reaction and bidirectional Sanger sequencing on all patient samples received by our laboratory for TPMT genotyping from August 2013 to November 2015.…”
mentioning
confidence: 99%